“Courtesy, respect, and follow through”: a mixed methods evaluation of faculty members’ experiences, needs, and approaches to research collaborations - Friedman, Daniela B.; Ek, Christina; Neils-Strunjas, Jean; Tanner, Andrea; Hebert, James R.; Donelle, Lorie; Levkoff, Sue E.; Hucek, Freda Allyson; Yelton, Brooks; Porter, Dwayne E. (Frontiers in Education, 2025)
IntroductionGuided by a communications-focused framework developed by an interdisciplinary team of authors, this paper presents data from a survey of health science faculty members to better understand how research collaborations are established and maintained.MethodsAn electronic survey was distributed to faculty in six colleges at a Research 1 institution. Quantitative data were downloaded into Excel and then RStudio for descriptive analysis. Open-ended, qualitative responses were coded and analyzed for themes.ResultsMost respondents were in public health (44.0%) or medicine (25.3%); 40.0% were tenured. A grant deadline was the main impetus reported for initiating research collaborations (86.1%). Most respondents (76.5%) sought federal research funding. Establishing roles at the start of collaborations was considered either extremely (74.4%) or somewhat (25.6%) valuable; most (78.0%) decided on roles in a collaborative manner. Women were significantly more likely than men to publish with community members (p < 0.001) and disseminate findings beyond journal publications or presentations (e.g., reports; p < 0.001). Individuals in public health were more likely than those in other disciplines to publish with community members (p = 0.026).DiscussionFindings suggest reaching out to collaborators to prepare a grant application no later than three months and ideally six months in advance. Expertise played a role in collaborator invitation, but personal qualities such as work ethic and enthusiasm for the research were also valued. Including and mentoring students on research teams was considered an important ingredient in research collaborations. Results should help guide efforts to establish and maintain research teams and may provide guidance to both novice and experienced researchers.